(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study examines the impact of social media endorsements and online identity on the e-commerce behavior of college students. Data from 273 students in Virudhunagar, Tamil Nadu, reveals that peer endorsements exert the strongest influence on purchasing decisions, followed by celebrity and influencer endorsements. Online identity factors, particularly social comparison and self-presentation, significantly shape e-commerce choices. Trust in endorsements, perceived social pressure (FOMO and social approval), and perceived self-congruity mediate these relationships. The findings offer valuable insights for brands targeting this demographic, emphasizing the importance of peer influence, trust, and identity alignment in social media